1997
DOI: 10.1085/jgp.110.5.565
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Calcium Inward Currents in Freshly Dissociated Smooth Myocytes of Rat Uterus

Abstract: Freshly dissociated myocytes from nonpregnant, pregnant, and postpartum rat uteri have been studied with the tight-seal patch-clamp method. The inward current contains both INa and ICa that are vastly different from those in tissue-cultured material. INa is abolished by Na+-free medium and by 1 μM tetrodotoxin. It first appears at ∼−40 mV, reaches maximum at 0 mV, and reverses at 84 mV. It activates with a voltage-dependent τ of 0.2 ms at 20 mV, and inactivates as a single exponential with a τ of 0.4 ms. Na+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
76
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 26 publications
(59 reference statements)
8
76
0
Order By: Relevance
“…The action was attributed to a decrease of L-type Ca 2+ channel activity, as mibefradil has a less potent action on these channels [58], and the authors noted the previous findings in rat tissue that T-type Ca 2+ channels could not be demonstrated [50][51][52]. However, using human myometrium, mibefradil also attenuated electrical and mechanical function by an action that could be separated from that of nifedipine.…”
Section: Myometriummentioning
confidence: 94%
See 1 more Smart Citation
“…The action was attributed to a decrease of L-type Ca 2+ channel activity, as mibefradil has a less potent action on these channels [58], and the authors noted the previous findings in rat tissue that T-type Ca 2+ channels could not be demonstrated [50][51][52]. However, using human myometrium, mibefradil also attenuated electrical and mechanical function by an action that could be separated from that of nifedipine.…”
Section: Myometriummentioning
confidence: 94%
“…These recordings were made using human myocytes from women undergoing either Caesarian section (non-labouring myometrium) or spontaneous vaginal delivery (labouring myometrium), showing that their presence was not only associated with tissue from the terminal stage of pregnancy. However, other groups report a TTX-sensitive Na + current, rather than a T-type Ca 2+ current, that accompanies L-type Ca 2+ current using pregnant and non-pregnant rat myometrium, as well as human cultured human cells [50][51][52]. This observation has been strengthened by measurement of the Na + channel gene product mNa v 2.3 in mouse myometrium [53].…”
Section: Myometriummentioning
confidence: 97%
“…Evidence has shown that, in vascular smooth muscle, action potentials are not dependent on Na + channels since tetrodotoxin (TTX) has no effect on amplitude and duration of action potentials [18], leading to the belief that these channels might not be present or prominent in these tissues. Nonetheless, Na + currents (I Na ) have been measured in visceral smooth muscles such as myometrium and uterus (pregnant), colon, esophagus, stomach, and ureter as well as in certain vascular smooth muscles such as the portal and azygos veins [2,8,[24][25][26]31,33,34]. The identification of functional voltage-gated Na + channels in quiescent and proliferating vascular smooth muscle cells (VSMC), however, has not been as forthcoming.…”
mentioning
confidence: 99%
“…Stimulation of isolated myocytes using voltage pulses revealed the current-voltage relationships of the pregnant myometrial SMCs in rats (18,34) and in humans (7,37). Application of single voltage pulses demonstrated that the Ca 2ϩ current (I Ca ) through L-type VOCCs significantly increased C Ca,i , whereas repetitive stimulation with pulse trains revealed that both VOCC opening and Ca 2ϩ -induced Ca 2ϩ release (CICR) from the sarcoplasmic reticulum (SR) are responsible for the increased C Ca,i (18).…”
mentioning
confidence: 99%
“…The entry current following depolarization of rat myometrial cells comprises two components, which were identified based on differences in their activation and inactivation properties as well as in their kinetics. The first component is a fast Na ϩ current (I Na ), while the second is a slow I Ca (34). Studies of the mechanisms responsible for the decay of C Ca,i in the pregnant rat myometrium, which is a critical process for SMC relaxation, showed that Ca 2ϩ pumps in the plasma membrane are responsible for 30% of the Ca 2ϩ extraction from the cell, and Na ϩ /Ca 2ϩ exchangers are responsible for up to 60%.…”
mentioning
confidence: 99%